Online Competency‐Based Assessment (OCBA): From Conceptual Model to Operational Authoring System - Amraouy, Mohammed; Ballafkih, Mostafa; Bennane, Abdellah; Himmi, Mohammed Majid (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Online learning has been growing continuously in the last decade, accelerated by the pandemic Coronavirus, in order to offer learners new possibilities for learning and to guarantee pedagogical continuity. But some aspects, including the learning assessment, are still in development and require profound changes to meet the demands of the 21st century. However, by taking advantage of artificial intelligence techniques and new learning theories, it would be possible to create an assessment system in accordance with the active learning approach. This paper illustrates the models, algorithms and design used to create a formative and summative assessment system that will be mobilized to evaluate learner’s knowledge, skills and competencies.